Parental role in children's sports activities in the context of achievement goal and self-determination theories - Kromerova, E. (Baltic Journal of Sport and Health Sciences, 2017)
Background. Aiming at understanding what influences youth sports experiences, researchers emphasize the significance of the role of the family not only in the decision to get engaged in sports activities, but also in the inclination to continue the activities. The increasing emphasis is on parental involvement and the impact of positive and negative verbal behaviour influence on the psychosocial state of children engaged in sport. The aim of this article was a conceptual overview of the family role, as the most significant microenvironment, in children`s sports activities. Methods. Analysis and discussion of scientific literature. Results. Parental behaviour entails different reactions of children engaged in sports, but on the basis of selfdetermination and achievement goal theories, it can be argued that the behaviour of the family should encourage athletes` mastery orientation, and consequently, a more pro-social conduct and moral reasoning can be expected. Conclusions. Systematic literature review showed that both theories are in favour of actions and strategy, with reference to parents` encouragement to involve children in a task, while reducing their ego functioning. It can be concluded that parents perceive their behaviour differently from that of their children, so often parents` positive reinforcement can have a negative impact on athletes` psychosocial state, values, behaviour and goal-setting at present and in the future.